Enhancing Early Childhood Learning Quality: A Qualitative Study on Teachers' Strategies and Pedagogical Approaches in Indonesian Preschools - Zamzami Zamzami; Sri Wahyuni; Reswita Reswita (STAI Hubbulwathan Duri, 2025)
Effective teaching strategies in early childhood education are essential for fostering both engagement and learning quality. However, there is a lack of focused research on how interactive methods specifically enhance young learners’ comprehension and participation. This qualitative study employed a descriptive approach to examine teaching strategies used by early childhood educators. Data were collected through semi-structured interviews with teachers, classroom observations, and document analysis to gather comprehensive insights. Findings indicate that educators utilize a range of interactive strategies, including play-based learning, storytelling, singing, field trips, and demonstrations. These approaches not only improve children's understanding of subject matter but also encourage active engagement and enjoyment in the learning process. The study highlights the importance of integrating interactive pedagogies to create a stimulating educational environment. It underscores the practical benefits of these methods in promoting both cognitive and social development in young learners. The research recommends that educators systematically incorporate interactive strategies into their teaching practices. Additionally, policymakers are encouraged to support educational models that prioritize engaging and participatory learning experiences. Future studies should investigate the long-term effects of these strategies on children's developmental outcomes.